A variação de ativos e retorno das ações no mercado de capitais brasileiro - Montes, Marcos Tadeu Ferreira (2010)
The finance literature has been found many relations between financial multiples and stock returns. We test the relation between asset growth and stock returns for the Brazilian capital market. Panel regressions were made to verify if this relations still significant in an emerging market like Brazil. The ability of asset growth as a predictor of stock returns was compared with other relevant financial multiples known in literature.